Determinant of Carbon Emission Disclosure at Mining Companies Listed in Indonesia Stock Exchange - Putri Halimah, N; Yanto, H (KnE Social Sciences, 2018)
This study aims to examine and obtain empirical evidence on determinants of carbon emissions disclosure at mining companies listed in Indonesia Stock Exchange. Several factors involved in this study, there are leverage, profitability, firm size, and institutional ownership. In addition, population of this study is 41 mining companies listed in Indonesia Stock Exchange. Meanwhile, sample is selected using purposive sampling technique which produced 56 unit of analysis. This study also uses content analysis techniques on annual reports and/or sustainability reports in 4 years to measure carbon emission disclosure. Data collection is conducted by documentation technique. Moreover, multiple rank regression with SPSS version 23 applications is executed to analyze the data. Results indicate that leverage, profitability, firm size, and institutional ownership have significant and negative effect on carbon emission disclosure. Therefore, it can be concluded that the higher leverage, profitability, firm size, and institutional ownership of the company, carbon emission disclosure which is reported by mining companies in Indonesia will be lower. Keywords: Carbon Emission Disclosure; Firm’s Size; Institutional Ownership; Leverage; Profitability